METHODS OF REGULATION OF MONEY TURNOVER STABILIZATION - Mardonova Ashirjon Tursunbayevna (Scholar Express Journals, 2022)
The article presents methods of regulation and stabilization of money circulation, money circulation, market economy, as well as purchasing power
Keywords: monetary circulation; inflation; method; money